Role of Helicobacter pylori eradication in the treatment of chronic idiopathic urticaria - Abdel Khalek H Younes; Khaled M Tawfik; Mohammed F Mohammed; Refaat Ragheb; Abeer A Abdel Tawaab; Khaled A Eid; Muhammad A Shawky (Wolters Kluwer Medknow Publications, 2018)
Background Chronic urticaria is a common immunological disorder, with a prevalence of 15-25%. Several exogenous and endogenous causes have been proposed as causative agents; one of them is infection of the gastrointestinal tract. Despite thorough investigation, the etiology remains unresolved in more than 80% of the cases. Objective The aim of the present study was to assess the prevalence of chronic idiopathic urticarial (CIU) patients presented with Helicobacter pylori infection and to study the effect of H. pylori eradication on the skin lesion in patients with CIU. Methodology This prospective study was carried out at the outpatient clinic of Dermatology Department of Al Azhar Assuit University Hospital on 30 patients with chronic urticaria (20 women and 10 men); their ages ranged from 16 to 65 years. The duration of the disease ranged from 6 weeks to 18 years. A primary diagnosis of CIU was made when an etiological factor accounting for the majority of the lesions could not be elucidated during the history-taking and physical examination. All the patients were subjected to careful history-taking at initial visit; physical examination to assess the number of urticaria wheals, size, and distribution, and associated angioedema; gastroscopy to obtain gastric mucosal biopsy from the antrum; and histopathological assessment of the gastric mucosal biopsy using hematoxylin and eosin, and Giemsa stains. The patients were scored according to the severity of disease (number of wheals, area of distribution, and the duration of the disease; itching and style of life; history of angioedema). The patients were treated for 2 weeks with amoxicillin (1 g/twice daily), metronidazole (500 mg/three doses daily), and omeprazole (20 mg/twice daily). All patients were followed up during the study duration of 3 months. To assess eradication efficacy, a repeated H. pylori stool antigen test was carried out for each patient 6 weeks after the end of anti-H. pylori therapy. Statistical analysis of the data was performed by using the SPSS_16 software. Results Fourteen patients (46.7%), aged less than 30 years, and 16 patients (53.3%), aged equal to or more than 30 years, were included in the present study. The mean of the ages of all patients was 34.9 years, and their age ranged from 16 to 65 years. There were 10 men (33.3%) and 20 women (66.7%). The mean of the duration of disease in all cases was 4 years, and ranged from 2 to 15 years. Nineteen patients presented with gastric symptoms. Seven patients (23.3%) had mild urticaria, 15 (50.0%) had moderate urticaria, and the remaining 8 (26.7%) had severe urticaria. Treatment results showed that 13 patients (43.3%) had complete remission, 12 patients (40.0%) had partial remission, and five patients (16.7%) showed no response. There was no statistically significant difference between age, sex, duration of illness, and gastric symptoms on the prognosis of urticaria after treatment. In addition, the results showed a highly statistically significant (P<0.01) difference between age categories and the gastric symptoms. The results also showed a statistically significant (P<0.05) difference between duration of disease and the gastric symptoms. Conclusion H. pylori infection is considered as a main cause of CIU, specifically in patients with gastric symptoms, and the eradication of H. pylori may help in the treatment of CIU.